Cell Specific Post-Translational Processing of Pikachurin, A Protein Involved in Retinal Synaptogenesis - Han, Jianzhong; Townes-Anderson, Ellen (PLOS ONE, 2012)
Pikachurin is a recently identified, highly conserved, extracellular matrix-like protein. Murine pikachurin has 1,017 amino acids (∼110 kDa), can bind to α-dystroglycan, and has been found to localize mainly in the synaptic cleft of photoreceptor ribbon synapses. Its knockout selectively disrupts synaptogenesis between photoreceptor and bipolar cells. To further characterize this synaptic protein, we used an antibody raised against the N-terminal of murine pikachurin on Western blots of mammalian and amphibian retinas and found, unexpectedly, that a low weight ∼60-kDa band was the predominant signal for endogenous pikachurin. This band was predicted to be an N-terminal product of post-translational cleavage of pikachurin. A similar sized protein was also detected in human Y79 retinoblastoma cells, a cell line with characteristics of photoreceptor cells. In Y79 cells, endogenous pikachurin immunofluorescence was found on the cell surface of living cells. The expression of the N-fragment was not significantly affected by dystroglycan overexpression in spite of the biochemical evidence for pikachurin-α-dystroglycan binding. The presence of a corresponding endogenous C-fragment was not determined because of the lack of a suitable antibody. However, a protein of ∼65 kDa was detected in Y79 cells expressing recombinant pikachurin with a C-terminal tag. In contrast, in QBI-HEK 293A cells, whose endogenous pikachurin protein level is negligible, recombinant pikachurin did not appear to be cleaved. Instead pikachurin was found either intact or as dimers. Finally, whole and N- and C-fragments of recombinant pikachurin were present in the conditioned media of Y79 cells indicating the secretion of pikachurin. The site of cleavage, however, was not conclusively determined. Our data suggest the existence of post-translational cleavage of pikachurin protein as well as the extracellular localization of cleaved protein specifically by retinal cells. The functions of the pikachurin N- and C-fragments in the photoreceptor ribbon synapse are unknown.